2016
DOI: 10.1007/s10694-016-0582-6
|View full text |Cite
|
Sign up to set email alerts
|

Fire Resistance and Post-fire Seismic Behavior of High Strength Concrete Shear Walls

Abstract: In this study, both fire tests and low-frequency cyclic loading tests after fire were conducted on three conventional high strength concrete (HSC) shear walls and a superimposed HSC shear wall with precast recycled aggregate concrete (RAC) panels. The RAC in this paper was made with recycled concrete aggregate. When specimens suffered the fire exposure on one side for 45 min, 90 min, and 135 min separately, spalling of concrete, temperature distribution and deformation of specimens were investigated as indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The mean residual cube and prism compressive strengths of HSC were reduced by 81.07 and 81.87% compared with those at ambient temperature, respectively. The comprehensive influence of the hydrate decomposition 27,28 and micro‐crack appearance caused by the pore pressure of the water evaporation 29,30 as well as the thermal incompatibility between the aggregate grain and the mortar 31 led to the strength reduction.…”
Section: Variability Of Hsc Compressive Strengthmentioning
confidence: 99%
“…The mean residual cube and prism compressive strengths of HSC were reduced by 81.07 and 81.87% compared with those at ambient temperature, respectively. The comprehensive influence of the hydrate decomposition 27,28 and micro‐crack appearance caused by the pore pressure of the water evaporation 29,30 as well as the thermal incompatibility between the aggregate grain and the mortar 31 led to the strength reduction.…”
Section: Variability Of Hsc Compressive Strengthmentioning
confidence: 99%
“…Previous investigations (Go et al, 2012;Hertz, 2018) showed that reinforced lightweight aggregate concrete walls outperformed reinforced normal weight concrete walls in terms of basic mechanical properties such as ultimate load, yield load and stiffness. In other experimental studies (Ngo et al, 2013;Xiao et al, 2017;Nguyen et al, 2018) on high-strength concrete walls exposed to fire, the results showed that high-strength concrete spalled more severely when exposed to fire compared to normalstrength concrete.…”
Section: Introductionmentioning
confidence: 84%
“…However, earthquake is also a credible hazard for the remaining lifespan of structures in seismic zones that may be repaired and reused after an accidental fire event. Currently there is no design guidance in this direction and only few experimental [19][20][21][22][23] and numerical [24][25][26] studies are available regarding the seismic/cyclic performance of fire-exposed RC structures.…”
Section: Introductionmentioning
confidence: 99%